ANALYSIS OF NEW PRODUCTION LINE PROJECT IMPROVEMENT THROUGH CRITICAL PATH METHOD (CPM), DESIGN STRUCTURE MATRIX (DSM) AND PROGRAM EVALUATION AND REVIEW (PERT) - Suryono, Yohanes Bangun; Hasbullah, Hasbullah (AGUSPATI Research Institute, 2020)
Implementing manufacturing projects involves many parties, using various resources and efforts, and facing difficult or even uncontrolled problems. Those indicate a need for planning tools or methods that can help manage resources effectively, which can help anticipate problems that will arise as soon as possible. There are projects in companies involved in the automotive parts manufacturing industry that perform poorly due to project implementation. Those are due to iterations and restructuring that took place and poor project implementation scheduling. The purpose of this research is to analyze and identify a series of activities and process time to build a new production line using Critical Path Method (CPM), Design Structure Matrix (DSM), and Evaluation and Review Technique (PERT) Program to be able to implement management targets. This study shows an increase in the construction of new production lines with the previous duration, four tears, 13 critical paths from 18 activities. At the same time, after the repair, a total time 185 days is total tears 0, 9 critical lines from 18 activities with a success rate of 90.1%. With this study's results, it recommends that companies with new production line construction projects consider using PERT-CPM techniques in project scheduling